مستقبل الاتحاد الأوروبي في ظل المتغيرات الدولية القائمة - بن سليمأ‌- فــرج علي (Aljameai, 2023)
المستخلص: يدرس البحث نشأة وتطور الاتحاد الأوروبي، والصعاب التي سببت له انقسامات داخلية كبيرة أثرت على تماسكه كالهجرة وخروج بريطانيا من الاتحاد، وعدم تقارب مؤسسات الاتحاد مع مواطنيه، وعجزه عن خلق سياسة خارجية موحدة إزاء القضايا الدولية الراهنة؛ ومحاولة استنباط مستقبل الاتحاد الأوروبي في ظل صراع الدول الكبار من خلال تناول التداعيات السياسية والاقتصادية للأزمة الأوكــرانية الروسية التي تظهر أبعادها الاستراتيجية من خلال تشابك مستوى علاقات دول الأزمة مع الاتحاد الأوروبي، حتى يحقق البحث نتائجه المرجوة بالوصول لتحليلات منطقية على أسس موضوعية سليمة. Abstract: The research examines the emergence and development of the European Union, as well as the challenges that have caused significant internal divisions that have affected its cohesion, such as immigration and the withdrawal of Britain from the Union. It also addresses the lack of convergence between the Union’s institutions and its citizens, and its inability to create a unified foreign policy regarding current international issues. The research also attempts to derive the future of the European Union in the context of the power struggle among major countries by examining the political and economic implications of the Russian-Ukrainian crisis, which reveals its strategic dimensions through the interplay of the crisis-affected countries with the European Union. The research aims to achieve its desired results by reaching logical analyses based on objective foundations.